(untitled) (Ustozlar uchun, 2026)
Disturbances of the intestinal microbiota are increasingly recognized as an important factor in the persistence of inflammation and progression of chronic viral hepatitis. Modulation of gut microbiota may represent a promising pathogenetic approach. Objective: To assess alterations of the intestinal microbiota in patients with chronic hepatitis B and C and to evaluate the clinical and laboratory effects of probiotic therapy containing Saccharomyces boulardii as an adjunct to standard treatment. Methods: A total of 70 patients with chronic viral hepatitis (40 with hepatitis B and 30 with hepatitis C) were enrolled. Patients were divided into two groups: a probiotic group (n=40), receiving standard therapy plus a probiotic containing Saccharomyces boulardii, and a control group (n=30), receiving standard therapy alone. Clinical symptoms, laboratory parameters, and bacteriological stool analyses were evaluated before and after treatment. Results: Intestinal dysbiosis was identified in all patients and was significantly associated with disease duration and severity of clinical manifestations. Patients receiving probiotic therapy demonstrated a marked improvement in intestinal microbiota composition, characterized by increased levels of beneficial bacteria and reduced opportunistic microorganisms, compared with the control group. Probiotic supplementation was associated with faster regression of gastrointestinal and systemic symptoms and a reduction in dysbiosis severity. The therapy was well tolerated, with no adverse events reported. Conclusions: Intestinal dysbiosis is a common finding in chronic viral hepatitis and correlates with disease duration and clinical severity. Adjunctive probiotic therapy containing Saccharomyces boulardii improves gut microbiota balance and clinical outcomes and may serve as an effective component of pathogenetic treatment in patients with chronic hepatitis B and C.